2023
DOI: 10.3389/fpsyt.2023.1095222
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with the risk of developing psychosis in a Mexican general population sample

Abstract: Epidemiological evidence has linked an array of sociodemographic and psychosocial factors with an increased risk of developing psychosis. However, research in samples from low- and middle-income countries is still scarce. This study used a Mexican sample to explore (i) sociodemographic and psychosocial differences between individuals with and without a positive screen for Clinical High-Risk for psychosis (CHR), and (ii) sociodemographic and psychosocial factors associated with screening positive for CHR. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 140 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…[52,53] Young people who went to war, escaping from such unfavorable family and social systems, and having experienced a series of traumatic experiences in the war, increased the risk of developing psychotic disorders according to the principle of the cumulative effect of trauma. [3,54,55] The severity of clinical presentation assessed using the PANSS questionnaire indicated that the age and witnessing abuse are significant influencing factor in emergence of psychotic disorder: younger participants and those who witnessed abuse had more pronounced psychotic symptomatology. The feeling of constant anticipation, mistrust and unfavorable growing conditions in war-traumatized families obviously led to serious mental damage and contributed to the development of productive symptomatology of psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52,53] Young people who went to war, escaping from such unfavorable family and social systems, and having experienced a series of traumatic experiences in the war, increased the risk of developing psychotic disorders according to the principle of the cumulative effect of trauma. [3,54,55] The severity of clinical presentation assessed using the PANSS questionnaire indicated that the age and witnessing abuse are significant influencing factor in emergence of psychotic disorder: younger participants and those who witnessed abuse had more pronounced psychotic symptomatology. The feeling of constant anticipation, mistrust and unfavorable growing conditions in war-traumatized families obviously led to serious mental damage and contributed to the development of productive symptomatology of psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 , 53 ] Young people who went to war, escaping from such unfavorable family and social systems, and having experienced a series of traumatic experiences in the war, increased the risk of developing psychotic disorders according to the principle of the cumulative effect of trauma. [ 3 , 54 , 55 ]…”
Section: Discussionmentioning
confidence: 99%